2021
DOI: 10.3390/ijms22168879
|View full text |Cite
|
Sign up to set email alerts
|

LRG1 Expression Is Elevated in the Eyes of Patients with Neovascular Age-Related Macular Degeneration

Abstract: Leucine-rich a-2-glycoprotein 1 (LRG1) is a candidate therapeutic target for treating the neovascular form of age-related macular degeneration (nvAMD). In this study we examined the expression of LRG1 in eyes of nvAMD patients. Choroidal neovascular membranes (CNVMs) from patients who underwent submacular surgery for retinal pigment epithelium–choroid graft transplantation were collected from 5 nvAMD patients without any prior intravitreal anti-VEGF injection, and from six patients who received intravitreal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Abnormal levels of LRG1 in the skin of diabetic mice delay the closure of chronic wounds through the formation of NETs [ 56 ], whose dysregulated function is known to cause cell damage in a number of conditions including diabetes [ 66 ]. Similarly, LRG1 has been reported to promote fibrosis in lung [ 16 , 67 ], kidney [ 68 ], dermal [ 34 , 67 , 69 ], and ocular tissues [ 57 , 70 , 71 ]. In particular, aberrant LRG1 levels were shown to promote ECM deposition both directly, through transactivation of resident fibroblasts [ 16 , 68 , 70 ] and epithelial cells [ 57 , 71 ], and indirectly by disrupting the formation of functional vessels [ 34 ] and modulating neutrophil pro-fibrotic effects [ 57 ] (Fig.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal levels of LRG1 in the skin of diabetic mice delay the closure of chronic wounds through the formation of NETs [ 56 ], whose dysregulated function is known to cause cell damage in a number of conditions including diabetes [ 66 ]. Similarly, LRG1 has been reported to promote fibrosis in lung [ 16 , 67 ], kidney [ 68 ], dermal [ 34 , 67 , 69 ], and ocular tissues [ 57 , 70 , 71 ]. In particular, aberrant LRG1 levels were shown to promote ECM deposition both directly, through transactivation of resident fibroblasts [ 16 , 68 , 70 ] and epithelial cells [ 57 , 71 ], and indirectly by disrupting the formation of functional vessels [ 34 ] and modulating neutrophil pro-fibrotic effects [ 57 ] (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, LRG1 has been reported to promote fibrosis in lung [ 16 , 67 ], kidney [ 68 ], dermal [ 34 , 67 , 69 ], and ocular tissues [ 57 , 70 , 71 ]. In particular, aberrant LRG1 levels were shown to promote ECM deposition both directly, through transactivation of resident fibroblasts [ 16 , 68 , 70 ] and epithelial cells [ 57 , 71 ], and indirectly by disrupting the formation of functional vessels [ 34 ] and modulating neutrophil pro-fibrotic effects [ 57 ] (Fig. 5 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Its relevance with respect to neovascular eye disease was first studied by Wang and colleagues, who showed that LRG1 mediates its angiogenic effects in murine models by modulating the TGF-beta signaling pathway in endothelial cells [50]. However, LRG1 has also come into focus in patients with neovascular AMD because elevated levels of LRG1 have been detected in the aqueous humor, vitreous, and CNV membranes of patients with nAMD [53][54][55]. This is of particular interest because the inhibition of LRG1 with a function-blocking antibody successfully inhibits laser-induced CNV in young mice [56], suggesting that anti-LRG1 therapy may be a promising therapeutic option for the treatment of nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression of five genes, serpina3n (serine protease inhibitor A3N), lcn2 (lipocalin-2), ackr1 (atypical chemokine receptor 1), LRG1, and lamc3 (laminin subunit gamma 3), were validated at the level of the inner blood retinal barrier cells (Lipski et al, 2020). The level of LRG1 obtained from eyes in patients with neovascular agerelated macular degeneration were increased, which indicated the target therapeutic therapy of anti-LRG1 monoclonal antibody (Mundo et al, 2021). LRG1 activated NADPH oxidase four to promote the epithelial mesenchymal transition of retinal pigment epithelium cells, which explored the potential mechanism for subretinal fibrosis in the basic experiment (Zhou et al, 2021).…”
Section: Part Five: Lrg1 Involved In Eye Diseasesmentioning
confidence: 96%